Monomolecular layer modified proton exchange membrane as well as preparation method and application thereof

By modifying a single layer on the proton exchange membrane of the flow battery and blocking metal ions with a single layer, the problem of reducing conductivity caused by the improvement of ion permeability in the prior art is solved, and the efficiency and energy of the flow battery are improved Utilization.

CN119297323APending Publication Date: 2025-01-10STATE POWER INVESTMENT CORP HYDROGEN ENERGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411498200.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

When the proton exchange membrane of existing flow batteries improves ion permeability, it often leads to a decrease in conductivity and affects battery efficiency.

Method used

Using a single-layer modified proton exchange membrane method, the esterification reaction of single-molecular end groups-OH and side chain sulfonic acid groups is carried out on perfluorosulfonic acid resin to form -OSO2- groups to form an ordered single molecule The layer is used to block metal ions migration, reduce ion permeability while maintaining conductivity.

Benefits of technology

Without increasing the resistance of the proton exchange membrane, the ion permeability of the electrolyte is significantly reduced, and the Coulomb efficiency and energy efficiency of the flow battery are improved. Compared with the commercial Nafion212 membrane, the vanadium ion permeability is reduced by one order of magnitude. The conductance is The rate remains the same.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297323A_ABST
    Figure CN119297323A_ABST
Patent Text Reader

Abstract

The invention provides a monomolecular layer modified proton exchange membrane as well as a preparation method and application thereof, and the preparation method of the monomolecular layer modified proton exchange membrane comprises the following steps: soaking a perfluorosulfonic acid proton exchange membrane in an acid solution containing monomolecules, and then performing washing and secondary drying to obtain the monomolecular layer modified proton exchange membrane, the single molecule includes a hydroxyl-terminated compound. According to the preparation method of the proton exchange membrane modified by the monomolecular layer, surface modification is carried out on a perfluorosulfonic acid proton exchange membrane by using a monomolecule, esterification reaction is carried out by using a monomolecule end group-OH and a side chain sulfonic acid group-SO3H of the proton exchange membrane to form a-OSO2-group, and the surface of the proton exchange membrane is modified by an ordered monomolecular layer, so that the proton exchange membrane modified by the monomolecular layer is obtained. The orderly-arranged monomolecular terminal group has good space barrier and repulsion effects on metal ions, migration and permeation of vanadium ions, iron ions and chromium ions can be inhibited, and meanwhile, the resistance of the proton exchange membrane is not increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of liquid flow batteries, and in particular to a monolayer-modified proton exchange membrane and a preparation method and application thereof. Background Art

[0002] With the rapid development of social economy, traditional fossil energy can no longer meet the needs of sustainable development of mankind. The large-scale consumption of fossil energy has caused a series of serious ecological and environmental problems. Therefore, energy reform is imminent. Only by taking renewable energy such as hydropower, wind power, solar energy, and nuclear power as the main energy source in the future can we fundamentally resolve the constraints of energy resources and the environment, realize the sustainable utilization of energy resources, and promote the sustainable development of mankind. Due to the volatility and intermittent characteristics of new energy, it is difficult to achieve full utilization. Energy storage has the function of smoothing new energy and filling the peak of the power grid, which is very critical to the development of new energy. Among them, liquid flow batteries have independent design of power and energy storage capacity, high safety, long life and environmental friendliness, and are a hot spot in the field of energy storage research.

[0003] Liquid flow batteries are mainly composed of electrolyte, electrodes, and diaphragms. As the core component of liquid flow batteries, diaphragms determine the efficiency and cycle life of liquid flow batteries. Perfluorosulfonic acid proton exchange membranes have good chemical stability and ion conductivity, and are the main diaphragm materials currently used in liquid flow batteries. During the battery charging and discharging process, the following requirements are placed on the diaphragm: First, the diaphragm needs to have high ion conductivity to form an ion transfer circuit inside the electrolyte and reduce battery polarization. Second, the diaphragm needs to block the penetration of positive and negative electrolytes to prevent the battery from self-discharging. The commercial proton membrane currently used in liquid flow batteries is the DuPont Nafion212 membrane, which is relatively expensive and has severe ion penetration.

[0004] At present, the methods for improving ion permeation are: 1) coating a surface modification layer of several microns or tens of microns on the surface of the proton membrane, 2) blending perfluorosulfonic acid resin with high molecular polymer, and 3) doping with inorganic substances. All three methods can inhibit ion permeation to a certain extent, but the surface modification layer usually has a low conductivity, which increases the overall resistance of the proton membrane. Blending perfluorosulfonic acid resin with high molecular polymer and doping with inorganic substances will reduce the conductivity of the diaphragm, resulting in reduced battery efficiency.

[0005] Therefore, it is necessary to develop a low-cost, high ion conductivity, and high ion selectivity membrane. Summary of the invention

[0006] The present application aims to solve the problem of improving the high ion permeability of the proton exchange membrane while not reducing the ion conductivity of the proton exchange membrane to a certain extent.

[0007] In view of this, an object of the present application is to provide a method for preparing a monolayer modified proton exchange membrane, firstly, a proton exchange membrane is prepared using a perfluorosulfonic acid resin, and then the surface of the proton exchange membrane is modified using a single molecule, and an esterification reaction is carried out between the monomolecule terminal group -OH and the proton exchange membrane side chain sulfonic acid group -SO3H to form an -OSO2- group, and an ordered monolayer is modified on the surface of the proton exchange membrane. The ordered arrangement of the monomolecule terminal groups has a good spatial barrier and repulsion effect on metal ions, and can inhibit the migration and penetration of vanadium ions, iron ions, and chromium ions. The monolayer can greatly reduce the ion permeability of the electrolyte without increasing the resistance of the proton exchange membrane, thereby improving the coulombic efficiency and energy efficiency of the liquid flow battery.

[0008] Another object of the present application is to provide a monolayer modified proton exchange membrane.

[0009] Another object of the present application is to provide a liquid flow battery.

[0010] To achieve the above objectives, the first aspect of the present application proposes a method for preparing a monolayer modified proton exchange membrane, comprising:

[0011] dissolving perfluorosulfonic acid resin in a solvent to obtain a polymer solution;

[0012] Scrape coating the polymer solution into a membrane, followed by a first drying step to obtain a perfluorosulfonic acid proton exchange membrane;

[0013] The perfluorosulfonic acid proton exchange membrane is immersed in an acid solution containing a single molecule, followed by washing and a second drying to obtain the single molecule layer modified proton exchange membrane; the single molecule includes a terminal hydroxyl compound.

[0014] In some embodiments, the terminal hydroxyl compound comprises a compound having a structure of Formula I:

[0015]

[0016] In formula I, R is one of hydroxyl, hydrocarbon, unsaturated hydrocarbon, imidazole and phenyl.

[0017] In some embodiments, the compound having the structure of Formula I includes at least one of Compounds 1 to 5:

[0018]

[0019] In some embodiments, in the acid solution containing single molecules, the mass content of the terminal hydroxyl compound is 5-10%.

[0020] In some embodiments, in the acid solution containing single molecules, the acid includes at least one of sulfuric acid and hydrochloric acid.

[0021] In some embodiments, the method for preparing the monolayer modified proton exchange membrane also includes the step of preparing an acid solution containing single molecules; the method for preparing the acid solution containing single molecules includes: dissolving the single molecules in the acid solution, dispersing them evenly, and obtaining the acid solution containing single molecules.

[0022] In some embodiments, the soaking time is 0.1-2 hours.

[0023] In some embodiments, the soaking temperature is 30-80°C.

[0024] In some embodiments, during the soaking process, the hydroxyl group at the end of the terminal hydroxyl compound undergoes an esterification reaction with the sulfonic acid group in the perfluorosulfonic acid resin to form an -OSO2- group.

[0025] In some embodiments, the perfluorosulfonic acid resin includes an H-type perfluorosulfonic acid resin.

[0026] In some embodiments, the solid content of the polymer dispersion is 10-30%.

[0027] In some embodiments, the solvent includes at least one of water, ethanol, and propanol.

[0028] In some embodiments, the base film used in the scraping coating process includes at least one of a polyethylene terephthalate base film, a polyimide base film, and a polyphenylene sulfide base film.

[0029] In some embodiments, the first drying temperature is 80-160° C., and the first drying time is 10-60 min.

[0030] In some embodiments, the perfluorosulfonic acid proton exchange membrane has a thickness of 50-60 μm.

[0031] In some embodiments, the second drying temperature is 30-80° C., and the second drying time is 8-24 hours.

[0032] In some embodiments, the detergent used for the washing includes at least one of water, ethanol, and propanol.

[0033] The second aspect of the present application provides a monolayer-modified proton exchange membrane, which is prepared using the method for preparing a monolayer-modified proton exchange membrane described in the present application.

[0034] In some embodiments, the monolayer in the monolayer modified proton exchange membrane contains -OSO2- groups.

[0035] In some embodiments, the structural formula of the monolayer in the monolayer-modified proton exchange membrane is as shown in Formula II:

[0036]

[0037] In formula II, R' is the perfluorosulfonic acid resin minus the sulfonic acid group, and R is one of hydroxyl, saturated hydrocarbon, unsaturated hydrocarbon, imidazole, and phenyl.

[0038] In some embodiments, the thickness of the monolayer in the monolayer-modified proton exchange membrane is 10-500 nm.

[0039] The third aspect of the present application provides a liquid flow battery, comprising an electrolyte, electrodes and a diaphragm, wherein the diaphragm is the monolayer-modified proton exchange membrane described in the present application.

[0040] In some embodiments, the flow battery comprises one of an all-vanadium flow battery and an iron-chromium flow battery.

[0041] The method for preparing the monolayer modified proton exchange membrane described in the present application can at least bring the following beneficial effects:

[0042] First, a proton exchange membrane is prepared using perfluorosulfonic acid resin, and then a single molecule is used to modify the surface of the proton exchange membrane. The single molecule end group -OH is used to react with the proton exchange membrane side chain sulfonic acid group -SO3H to form an -OSO2- group, and an ordered monolayer is modified on the surface of the proton exchange membrane. This ordered arrangement of the monomolecule end group (that is, the R group in Formula I and Formula II) has a good spatial barrier and repulsive effect on metal ions, and can inhibit the migration and penetration of vanadium ions, iron ions, and chromium ions. The monolayer can greatly reduce the ion permeability of the electrolyte without increasing the resistance of the proton exchange membrane, thereby improving the coulombic efficiency and energy efficiency of the flow battery. Among them:

[0043] The conductivity of the prepared monolayer modified proton exchange membrane reached 0.12S / cm@25℃, 100%RH, and the vanadium ion permeability was 1.2*10 -7 cm 2 / min, compared with the commercial Nafion212 membrane (conductivity 0.12S / cm@25℃-100%RH, ion permeability 1.4*10 -6 cm 2 / min) and the preparation of proton exchange membrane B without monolayer modification (conductivity 0.12S / cm@25℃-100%RH, ion permeability 1.5*10 -6 cm2 / min), the ion permeability decreases by one order of magnitude, while the conductivity remains unchanged.

[0044] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings.

[0046] in:

[0047] Figure 1 This is a flow chart of a method for preparing a monolayer modified proton exchange membrane according to an exemplary embodiment of the present application.

[0048] Figure 2 for Figure 1 Schematic diagram of the process of step S103 in FIG.

[0049] Reference numerals:

[0050] 1-perfluorosulfonic acid proton exchange membrane; 2-monomolecule molecular structure (ie, compound having the structure of formula I); 3-monomolecule modified proton exchange membrane; 301-monolayer. DETAILED DESCRIPTION

[0051] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.

[0052] In this application, the disclosure of numerical ranges includes all values ​​within the entire range and the disclosure of further subdivided ranges, including the endpoints and sub-ranges given in these ranges.

[0053] In this application, the raw materials, equipment, etc. involved, unless otherwise specified, are all raw materials and equipment that can be made through commercial channels or known methods; the methods involved, unless otherwise specified, are all conventional methods.

[0054] In the present application, "normal temperature" refers to 20-30°C.

[0055] <Method for preparing monolayer modified proton exchange membrane>

[0056] The inventors found that there are currently three ways to improve ion permeation: 1) coating a surface modification layer of several microns and tens of microns on the surface of the proton membrane; 2) using perfluorosulfonic acid resin and high molecular polymer blending; 3) using inorganic doping. All three methods can inhibit ion permeation to a certain extent, but the surface modification layer usually has a low conductivity, resulting in an increase in the overall resistance of the proton membrane. Using perfluorosulfonic acid resin and high molecular polymer blending and using inorganic doping will reduce the conductivity of the diaphragm, resulting in reduced battery efficiency.

[0057] In response to the above findings, the inventors further discovered that by using single-molecule monolayer modification, an ordered monolayer is modified on the surface of the proton membrane through chemical reaction. The thickness of the molecular layer is only nanometers and its resistance is negligible. This kind of ordered arrangement of single-molecule terminal groups has good spatial barrier and repulsion effects on metal ions, which can improve the problem of high ion permeability of the proton membrane without increasing the resistance of the proton membrane.

[0058] A method for preparing a monolayer modified proton exchange membrane according to an embodiment of the present application is described below with reference to the accompanying drawings.

[0059] Figure 1 This is a flow chart of a method for preparing a monolayer modified proton exchange membrane according to an exemplary embodiment of the present application.

[0060] like Figure 1 As shown, the method for preparing the monolayer modified proton exchange membrane of the embodiment of the present application comprises the following steps:

[0061] S101, dissolving perfluorosulfonic acid resin in a solvent to obtain a polymer solution.

[0062] In some embodiments, the perfluorosulfonic acid resin includes but is not limited to H-type perfluorosulfonic acid resin and the like.

[0063] As an optional example, the perfluorosulfonic acid resin is an H-type perfluorosulfonic acid resin that is soluble at room temperature.

[0064] In some embodiments, the solid content of the polymer dispersion is 10-30%, including but not limited to 10%, 15%, 20%, 25% or 30%.

[0065] In some embodiments, the solvent includes but is not limited to at least one of water, ethanol, propanol, and the like.

[0066] As an optional example, perfluorosulfonic acid resin is dissolved in a solvent to form a uniformly dispersed polymer solution.

[0067] S102, coating the polymer solution into a membrane by scraping, and then performing a first drying to obtain a perfluorosulfonic acid proton exchange membrane.

[0068] In some embodiments, the base film used in the scraping film forming process includes but is not limited to at least one of a polyethylene terephthalate base film, a polyimide base film, a polyphenylene sulfide base film, and the like.

[0069] As an optional example, the base film used in the scraping coating process is a polyethylene terephthalate (PET) base film.

[0070] In the embodiments of the present application, there is no limitation on the thickness of the base film used in the scraping film-forming process, and the thickness of the base film used for scraping film-forming in the art can be any thickness.

[0071] In some embodiments, the first drying temperature is 80-160°C, including but not limited to 80°C, 100°C, 120°C, 140°C or 160°C, etc.

[0072] In some embodiments, the first drying time is 10-60 min, including but not limited to 10 min, 20 min, 30 min, 40 min, 50 min or 60 min, etc.

[0073] In some embodiments, the first drying method includes but is not limited to at least one of oven drying, vacuum drying, spray drying, etc.

[0074] In some embodiments, the thickness of the perfluorosulfonic acid proton exchange membrane is 50-60 μm, including but not limited to 50 μm, 52 μm, 55 μm, 57 μm or 60 μm.

[0075] As an optional example, step S102 is: coating the polymer solution on a PET base film to form a film, and drying the wet film in an oven at 80-160° C. for 10-60 min to obtain a perfluorosulfonic acid proton exchange membrane.

[0076] S103, soaking the perfluorosulfonic acid proton exchange membrane in an acid solution containing a single molecule, followed by washing and a second drying to obtain the proton exchange membrane modified with the single molecule layer; the single molecule includes a terminal hydroxyl compound (such as Figure 2 shown).

[0077] In the embodiments of the present application, the terminal hydroxyl compound may be a compound having a hydroxyl group (—OH) at one end in the structural formula, or may be a compound having a plurality of hydroxyl groups (—OH) at multiple ends in the structural formula.

[0078] In some embodiments, the terminal hydroxyl compound comprises a compound having a structure of Formula I:

[0079]

[0080] In formula I, R is one of hydroxyl, hydrocarbon, unsaturated hydrocarbon, imidazole and phenyl.

[0081] Exemplarily, the saturated hydrocarbon group includes chain alkyl, branched alkyl and cycloalkyl, and the unsaturated hydrocarbon group includes alkenyl, alkynyl, cycloalkenyl and the like.

[0082] As an optional example, R is a hydroxyl group, a hydrocarbon group having 1 to 5 carbon atoms (for example, methyl, ethyl, n-propyl, isopropyl, cyclopropyl, butyl, cyclobutyl, etc.), an unsaturated hydrocarbon group having 2 to 5 carbon atoms (for example, vinyl, propenyl, cyclopropenyl, butenyl, cyclobutenyl, cyclopentadienyl, etc.), an imidazolyl group, or a phenyl group.

[0083] As a preferred example, the compound having the structure of Formula I includes but is not limited to at least one of Compounds 1 to 5, etc.:

[0084]

[0085] As a more preferred example, the single molecule is a terminal hydroxyl compound, and the terminal hydroxyl compound is at least one of Compound 1 to Compound 5.

[0086] In some embodiments, the mass content of the terminal hydroxyl compound in the acid solution containing a single molecule is 5-10%. In the embodiment of the present application, the mass content of the terminal hydroxyl compound in the acid solution containing a single molecule is within the above range, which can reduce the soaking time and the number of washing times; if it is less than 5%, the soaking reaction time is extended by more than 0.5h; if it is higher than 10%, the number of washing times is increased by more than 3 times.

[0087] In some embodiments, in the acid solution containing single molecules, the acid includes but is not limited to at least one of sulfuric acid, sulfuric acid, and the like.

[0088] As an optional example, the acid in the acid solution containing single molecules is sulfuric acid, for example, 40-98 wt % H 2 SO 4 .

[0089] In some embodiments, the method for preparing the monolayer-modified proton exchange membrane further comprises the step of preparing an acid solution containing the monomolecule.

[0090] Exemplarily, the method for preparing the acid solution containing the single molecule includes: dissolving the single molecule in an acid solution, dispersing the single molecule evenly, and obtaining the acid solution containing the single molecule.

[0091] In some embodiments, the soaking time is 0.1-2 hours, including but not limited to 0.1 hours, 0.5 hours, 1 hour, 1.5 hours or 2 hours.

[0092] In some embodiments, the soaking temperature is 30-80°C, including but not limited to 30°C, 40°C, 50°C, 60°C, 70°C or 80°C.

[0093] In some embodiments, the soaking temperature is provided by heating in a water bath.

[0094] In some embodiments, during the soaking process, the hydroxyl group at the end of the terminal hydroxyl compound undergoes an esterification reaction with the sulfonic acid group in the perfluorosulfonic acid resin to form an -OSO2- group.

[0095] Specifically, the reaction principle of the above esterification reaction to form -OSO2- group is:

[0096]

[0097] Wherein the reactants are a perfluorosulfonic acid resin (e.g., H-type perfluorosulfonic acid resin) and a single molecule, R' is a perfluorosulfonic acid resin (e.g., H-type perfluorosulfonic acid resin) without the sulfonic acid group, and R is one of a hydroxyl group, a saturated hydrocarbon group, an unsaturated hydrocarbon group, an imidazole group, and a phenyl group (R here is the same as R in the compound of the above-mentioned formula I structure, and R-CH2-CH2-OH is another expression of the compound of the above-mentioned formula I structure, That is, Formula II below).

[0098] In some embodiments, the second drying temperature is 30-80°C, including but not limited to 30°C, 40°C, 50°C, 60°C, 70°C or 80°C.

[0099] In some embodiments, the second drying time is 8-24 hours, including but not limited to 8 hours, 12 hours, 16 hours, 20 hours or 24 hours.

[0100] In some embodiments, the detergent used for the washing includes but is not limited to at least one of water, ethanol, propanol, etc., preferably water.

[0101] In some embodiments, the second drying method includes but is not limited to at least one of oven drying, vacuum drying, spray drying, etc.

[0102] The preparation method of the monolayer modified proton exchange membrane of the embodiment of the present application is to first use perfluorosulfonic acid resin to prepare the proton exchange membrane, and then use a single molecule to modify the surface of the proton exchange membrane, and use the monomolecule end group -OH to react with the proton exchange membrane side chain sulfonic acid group -SO3H to form an -OSO2- group, and modify a layer of ordered monolayer on the surface of the proton exchange membrane. This ordered arrangement of monomolecule end groups (that is, R groups in formula I and formula II) has a good spatial barrier and repulsive effect on metal ions, which can inhibit the migration and penetration of vanadium ions, iron ions, and chromium ions. The monolayer can greatly reduce the ion permeability of the electrolyte without increasing the resistance of the proton exchange membrane, thereby improving the coulombic efficiency and energy efficiency of the flow battery. Wherein:

[0103] The conductivity of the prepared monolayer modified proton exchange membrane reached 0.12S / cm@25℃, 100%RH, and the vanadium ion permeability was 1.2*10- 7 cm 2 / min, compared with the commercial Nafion212 membrane (conductivity 0.12S / cm@25℃-100%RH, ion permeability 1.4*10- 6 cm 2 / min) and the preparation of proton exchange membrane B without monolayer modification (conductivity 0.12S / cm@25℃-100%RH, ion permeability 1.5*10- 6 cm 2 / min), the ion permeability decreases by one order of magnitude, while the conductivity remains unchanged.

[0104] <Monolayer modified proton exchange membrane>

[0105] The monolayer-modified proton exchange membrane of the embodiment of the present application is prepared by the method for preparing the monolayer-modified proton exchange membrane of the embodiment of the present application.

[0106] It can be understood that the monomolecular layer modified proton exchange membrane of the embodiment of the present application includes the above-mentioned perfluorosulfonic acid proton exchange membrane and the monomolecular modified layer formed on the above-mentioned perfluorosulfonic acid proton exchange membrane.

[0107] In some embodiments, the monolayer in the monolayer modified proton exchange membrane contains -OSO2- groups.

[0108] In some embodiments, the structural formula of the monolayer in the monolayer-modified proton exchange membrane is as shown in Formula II:

[0109]

[0110] In formula II, R' is the perfluorosulfonic acid resin minus the sulfonic acid group, and R is one of hydroxyl, saturated hydrocarbon, unsaturated hydrocarbon, imidazole, and phenyl.

[0111] In some embodiments, the thickness of the monolayer is 10-500 nm, including but not limited to 10 nm, 50 nm, 100 nm, 200 nm, 300 nm, 400 nm or 500 nm.

[0112] <Flow Battery>

[0113] The liquid flow battery of the embodiment of the present application includes an electrolyte, an electrode and a diaphragm, and the diaphragm is a proton exchange membrane modified with a single molecular layer of the embodiment of the present application.

[0114] In some embodiments, the flow battery includes but is not limited to one of an all-vanadium flow battery, an iron-chromium flow battery, and the like.

[0115] In the embodiments of the present application, there is no limitation on the specific selection of electrolytes and electrodes, which can be any electrolytes, electrodes, etc. used for corresponding liquid flow batteries in the art.

[0116] The monolayer-modified proton exchange membrane and liquid flow battery of the embodiments of the present application both have at least the beneficial effects of the monolayer-modified proton exchange membrane of the embodiments of the present application.

[0117] Certain features of the present technology are further illustrated in the following non-limiting examples.

[0118] The compounds involved in the following examples are all selected from the following compounds.

[0119]

[0120] The test method for metal ion permeability is: use a metal ion permeability test fixture and a UV-visible spectrophotometer to test the metal ion permeability. Taking vanadium ions as an example, add a 1.5mol / L VOSO4+3mol / LH2SO4 aqueous solution and a blank reference solution: a 1.5mol / L MgSO4+3mol / L H2SO4 aqueous solution to both sides of the fixture. The solution is stirred with a magnetic device and the concentration values ​​are tested after 30min, 50min, 70min, 90min and 110min respectively. A total of 6 data points are obtained. The changes in metal ion concentration in the semi-permeable cell are obtained through sampling tests. The ion permeability (D) of the membrane can be calculated by formula (1):

[0121]

[0122] In formula (1):

[0123] CA(0) is the concentration of the ion to be measured on the electrolyte side of the conductivity cell at the initial moment, in moles per cubic centimeter (mol / cm 3 );

[0124] CB(t) – the concentration of the ion to be measured on the permeate side of the conductivity cell at time t, in moles per cubic centimeter (mol / cm3);

[0125] VB - the volume of the permeate on the permeate side of the conductivity cell, in cubic centimeters (cm 3 );

[0126] S——The effective area of ​​the film sample to be tested, in square centimeters (cm 2 );

[0127] d——the thickness of the film sample to be tested, in centimeters (cm);

[0128] D——Ion diffusion coefficient of the ion to be measured in the membrane (cm 2 / s).

[0129] The conductivity test method is: using an electrochemical AC workstation and an AC impedance four-electrode method to measure the membrane internal resistance of the water electrolysis membrane, using an AC frequency of minimum 1 Hz, maximum 1 MHz, and a perturbation voltage of 10 mV. The wet thickness of the membrane is obtained by measuring the membrane after the test. The test temperature / humidity is 25°C-100% RH. The conductivity is calculated by the membrane conductivity through the formula δ=L / (RS), where δ is the membrane conductivity, L is the membrane thickness, R is the membrane test resistance, and S is the effective test area.

[0130] The coulombic efficiency and voltage efficiency test method is as follows: the prepared diaphragm (i.e., proton exchange membrane) is assembled on a stack with an electrode active area of ​​5cm*5cm (the electrolyte is a mixed solution of 1.5M trivalent vanadium sulfate solution and 3M sulfuric acid, and the electrolyte dosage is 40ml; graphite felt electrodes and graphite bipolar plates are used) to test the charge and discharge performance. The charge cut-off voltage is 1.6V, the discharge cut-off voltage is 1.0V, and the test condition is 120mA / cm 2 , the test temperature is 30℃, and the data of charging and discharging ampere-hour capacity, discharge ampere-hour capacity, charging energy, discharge energy, etc. are obtained. The coulomb efficiency of the battery stack is calculated according to the formula η a =A d / A c , η a is the Coulomb efficiency of the battery stack, A d is the discharge ampere-hour capacity of the battery stack, A c is the charging ampere-hour capacity of the battery stack, and the energy efficiency of the battery stack is calculated according to the formula η e =E d / E c , η e is the stack energy efficiency, Ed E is the discharge ampere-hour capacity of the battery stack, c is the charging ampere-hour capacity of the battery stack, and the voltage efficiency of the battery stack is calculated according to the formula η u =η e / η a , η e is the stack energy efficiency, η a is the coulombic efficiency of the battery stack.

[0131] Example 1

[0132] The method for preparing the monolayer modified proton exchange membrane of this embodiment comprises the following steps:

[0133] (1) A room temperature soluble H-type perfluorosulfonic acid resin was dissolved in a mixed solvent of water and n-propanol (mass ratio of water:n-propanol=1:2) to form a uniformly dispersed polymer solution with a solid content of 20%. The obtained solution was coated on a PET base film to form a film. The wet film was dried in an oven at 80°C for 10 min and then dried in an oven at 160°C for another 10 min to obtain a perfluorosulfonic acid proton exchange membrane with a thickness of 50 μm, which was marked as proton exchange membrane A1.

[0134] (2) The single molecule is dissolved in 60 wt % H2SO4 in a certain proportion to form a uniform dispersion (i.e., an acid solution containing the single molecule), the single molecule accounts for 5 wt % of the dispersion, and the single molecule is compound 1.

[0135] (3) The proton exchange membrane A obtained in step (1) is immersed in the dispersion formed in step (2) for 30 minutes, and heated in a water bath at a temperature of 50°C. After being taken out, it is washed with water and dried at a drying temperature of 80°C for 24 hours to obtain a proton exchange membrane modified with a single molecule, which is marked as proton exchange membrane B1. During the immersion process, -OH at the end of the single molecule undergoes an esterification reaction with -SO3H in the perfluorosulfonic acid resin to form an -OSO2- group; the thickness of the single molecule layer is 50nm.

[0136] Examples 2-5 are basically the same as Example 1, except that: the single molecules are selected differently, and the proton exchange membranes prepared in Examples 2-5 are named proton exchange membranes B2-B5 according to the different single molecules, as shown in Table 1.

[0137] The vanadium ion permeability and conductivity of the proton exchange membrane A1, the proton exchange membranes B2-B5 prepared in Examples 1-5, and the commercial Nafion 212 membrane were tested respectively. The test results are shown in Table 1.

[0138] Table 1

[0139]

[0140]

[0141] As can be seen from Table 1, the ion conductivity and vanadium ion permeability of the prepared proton exchange membrane A1 are comparable to those of Nafion212. After single-molecule surface modification, the vanadium ion permeability of the proton exchange membranes prepared in Examples 1-5 is significantly reduced, and the conductivity does not change significantly. The vanadium ion permeability of the proton exchange membrane B4 is 1.2*10 -7 cm 2 / min, conductivity is 0.124S / cm.

[0142] Example 6

[0143] The method for preparing the monolayer modified proton exchange membrane of this embodiment comprises the following steps:

[0144] (1) A room temperature soluble H-type perfluorosulfonic acid resin was dissolved in a mixed solvent of water and n-propanol (mass ratio of water:n-propanol=1:2) to form a uniformly dispersed polymer solution with a solid content of 20%. The obtained solution was coated on a PET base film to form a film. The wet film was dried in an oven at 80°C for 10 min and then dried in an oven at 160°C for another 20 min to obtain a perfluorosulfonic acid proton exchange membrane with a thickness of 50 μm, which was marked as proton exchange membrane A2.

[0145] (2) The single molecule is dissolved in 60 wt % H2SO4 in a certain proportion to form a uniform dispersion (i.e., an acid solution containing the single molecule), the single molecule accounts for 5 wt % of the dispersion, and the single molecule is compound 1.

[0146] (3) The proton exchange membrane A obtained in step (1) is immersed in the dispersion formed in step (2) for 20 minutes, and heated in a water bath at a temperature of 60°C. After being taken out, it is washed with water and dried at a drying temperature of 80°C for 12 hours to obtain a proton exchange membrane modified with a single molecule, which is marked as proton exchange membrane B6. During the immersion process, -OH at the end of the single molecule undergoes an esterification reaction with -SO3H in the perfluorosulfonic acid resin to form an -OSO2- group; the thickness of the single molecule layer is 80nm.

[0147] Examples 7-10 are basically the same as Example 6, except that: the single molecules are selected differently, and the proton exchange membranes prepared in Examples 7-10 are named proton exchange membranes B7-B10 according to the different single molecules, as shown in Table 2.

[0148] The iron ion permeability and conductivity of the proton exchange membrane A2, the proton exchange membranes B7-B10 prepared in Examples 7-10, and the commercial Nafion 212 membrane were tested respectively. The test results are shown in Table 2.

[0149] Table 2

[0150]

[0151]

[0152] As can be seen from Table 2, the prepared proton exchange membrane A2 and Nafion212 are 0.125S / cm and 0.124S / cm respectively, and the iron ion permeability is 5.2*10 -6 cm 2 / min、5.6*10 -6 cm 2 / min, there is no significant difference in the conductivity and iron ion permeability between proton exchange membrane A and Nafion212, while after single molecule surface modification of Examples 6-10, the iron ion permeability of the proton exchange membrane is significantly reduced, and the conductivity has no significant change, among which the iron ion permeability of proton exchange membrane B9 is 3.1*10 -8 cm 2 / min, and the conductivity is 0.124S / cm. After single-molecule surface modification, the ion permeability of the proton exchange membrane is reduced by one order of magnitude, and the conductivity has no significant change.

[0153] Embodiment 11

[0154] The method for preparing the monolayer modified proton exchange membrane of this embodiment comprises the following steps:

[0155] (1) A room temperature soluble H-type perfluorosulfonic acid resin was dissolved in a mixed solvent of water and n-propanol (mass ratio of water:n-propanol=1:2) to form a uniformly dispersed polymer solution with a solid content of 25%. The obtained solution was coated on a PET base film to form a film. The wet film was dried in an oven at 80°C for 10 min and then dried in an oven at 160°C for another 30 min to obtain a perfluorosulfonic acid proton exchange membrane with a thickness of 50 μm, which was marked as proton exchange membrane A3.

[0156] (2) The single molecule is dissolved in 60 wt % H2SO4 in a certain proportion to form a uniform dispersion (i.e., an acid solution containing the single molecule), the single molecule accounts for 5 wt % of the dispersion, and the single molecule is compound 1.

[0157] (3) The proton exchange membrane A obtained in step (1) is immersed in the dispersion formed in step (2) for 30 minutes, and heated in a water bath at a temperature of 30°C. After being taken out, it is washed with water and dried at a drying temperature of 80°C for a drying time of 12 hours to obtain a proton exchange membrane modified with a single molecule, which is marked as proton exchange membrane B11. During the immersion process, -OH at the end of the single molecule undergoes an esterification reaction with -SO3H in the perfluorosulfonic acid resin to form an -OSO2- group; the thickness of the single molecule layer is 100 nm.

[0158] Examples 12-15 are basically the same as Example 11, except that: the single molecules are selected differently, and the proton exchange membranes prepared in Examples 12-15 are named proton exchange membranes B12-B15 according to the different single molecules, as shown in Table 3.

[0159] The chromium ion permeability and conductivity of the proton exchange membrane A3, the proton exchange membranes B12-B15 prepared in Examples 12-15, and the commercial Nafion 212 membrane were tested respectively. The test results are shown in Table 3.

[0160] Table 3

[0161]

[0162]

[0163] As can be seen from Table 3, the prepared proton exchange membrane A3 and Nafion212 are 0.118S / cm and 0.114S / cm respectively, and the chromium ion permeability is 1.2*10 -6 cm 2 / min, 1.3*10 -6 cm 2 / min, there is no significant difference in the conductivity and iron ion permeability between proton exchange membrane A and Nafion212, while after single molecule surface modification of Examples 11-15, the chromium ion permeability of the proton exchange membrane is significantly reduced, and the conductivity has no significant change, among which the iron ion permeability of proton exchange membrane B14 is 1.1*10 -7 cm2 / min, conductivity is 0.117S / cm.

[0164] Example 16

[0165] The method for preparing the monolayer modified proton exchange membrane of this embodiment comprises the following steps:

[0166] (1) A room temperature soluble H-type perfluorosulfonic acid resin was dissolved in a mixed solvent of water and n-propanol (mass ratio of water:n-propanol=1:2) to form a uniformly dispersed polymer solution with a solid content of 25%. The obtained solution was coated on a PET base film to form a film. The wet film was dried in an oven at 110°C for 10 min and then dried in an oven at 160°C for another 20 min to obtain a perfluorosulfonic acid proton exchange membrane with a thickness of 50 μm, which was marked as proton exchange membrane A4.

[0167] (2) The single molecule is dissolved in 60 wt % H2SO4 in a certain proportion to form a uniform dispersion (i.e., an acid solution containing the single molecule), the single molecule accounts for 10 wt % of the dispersion, and the single molecule is compound 1.

[0168] (3) The proton exchange membrane A obtained in step (1) is immersed in the dispersion formed in step (2) for 10 minutes, and heated in a water bath at a temperature of 80°C. After being taken out, it is washed with water and dried at a drying temperature of 80°C for 24 hours to obtain a proton exchange membrane modified with a single molecule, which is marked as proton exchange membrane B16. During the immersion process, -OH at the end of the single molecule undergoes an esterification reaction with -SO3H in the perfluorosulfonic acid resin to form an -OSO2- group; the thickness of the single molecule layer is 85nm.

[0169] Examples 17-20 are basically the same as Example 16, except that: the single molecules are selected differently, and the proton exchange membranes prepared in Examples 17-20 are named proton exchange membranes B16-B20 according to the different single molecules, as shown in Table 4.

[0170] The battery coulombic efficiency and voltage efficiency tests were performed on the proton exchange membrane A4, the proton exchange membranes B12-B15 prepared in Examples 12-15, and the commercial Nafion212 membrane. The electrode active area was 5×5 cm 2 , the test current density is 120mA / cm 2 , the test results are shown in Table 4.

[0171] Table 4

[0172]

[0173] As can be seen from Table 4, the coulombic efficiencies of the prepared proton exchange membranes A4 and Nafion212 are 96.6% and 96.5%, respectively, and the voltage efficiencies are 90.4% and 90.5%, respectively, with no significant difference between the two. After single-molecule surface modification of Examples 16-20, the coulombic efficiency of the proton exchange membranes is improved, and the voltage efficiency is not significantly reduced. Among them, the proton exchange membrane B19 has a coulombic efficiency of 98.1% and a voltage efficiency of 90.2%.

[0174] Example 21 (solid content in perfluorosulfonic acid resin dispersion is lower limit 10%)

[0175] This embodiment is basically the same as Embodiment 1, except that:

[0176] In step (1), the solid content of the solution is 10%, and the obtained perfluorosulfonic acid proton exchange membrane is marked as proton exchange membrane A5.

[0177] In step (3), the obtained single-molecule modified proton exchange membrane is marked as proton exchange membrane B21.

[0178] Example 22 (the content of single molecules in the acid solution containing single molecules is an intermediate value)

[0179] This embodiment is basically the same as Embodiment 1, except that:

[0180] In step (2), the single molecule accounts for 7.5 wt % in the dispersion.

[0181] In step (3), the obtained single-molecule modified proton exchange membrane is marked as proton exchange membrane B22.

[0182] Example 23 (the acid concentration in the acid solution containing a single molecule is the lower limit)

[0183] This embodiment is basically the same as Embodiment 1, except that:

[0184] In step (2), a single molecule is dissolved in 40 wt % H 2 SO 4 according to a certain ratio.

[0185] In step (3), the obtained single-molecule modified proton exchange membrane is marked as proton exchange membrane B23.

[0186] Example 24 (the acid concentration in the acid solution containing a single molecule is the lower limit)

[0187] This embodiment is basically the same as Embodiment 1, except that:

[0188] In step (2), a single molecule is dissolved in 98 wt % H 2 SO 4 according to a certain ratio.

[0189] In step (3), the obtained single-molecule modified proton exchange membrane is marked as proton exchange membrane B24.

[0190] Embodiment 25 (immersion time upper limit)

[0191] This embodiment is basically the same as Embodiment 1, except that:

[0192] In step (3), the proton exchange membrane A obtained in step (1) is immersed in the dispersion formed in step (2) for 2 hours to obtain a single-molecule modified proton exchange membrane, which is marked as proton exchange membrane B25.

[0193] Example 26 (intermediate soaking time)

[0194] This embodiment is basically the same as Embodiment 1, except that:

[0195] In step (3), the proton exchange membrane A obtained in step (1) is immersed in the dispersion formed in step (2) for 1 hour to obtain a single-molecule modified proton exchange membrane, which is marked as proton exchange membrane B26.

[0196] Embodiment 27 (immersion time lower limit)

[0197] This embodiment is basically the same as Embodiment 1, except that:

[0198] In step (3), the proton exchange membrane A obtained in step (1) is immersed in the dispersion formed in step (2) for 6 minutes to obtain a single-molecule modified proton exchange membrane, which is marked as proton exchange membrane B27.

[0199] Example 28 (single molecule, non-preferred single molecule)

[0200] This embodiment is basically the same as Embodiment 1, except that:

[0201] In step (2), a single molecule is

[0202] In step (3), the obtained single-molecule modified proton exchange membrane is marked as proton exchange membrane B28.

[0203] In summary, the method for preparing a single-molecule modified proton exchange membrane in the embodiment of the present application modifies the surface of the proton exchange membrane with a single molecule having a specific group (terminal hydroxyl group), thereby reducing the metal ion permeability of the proton exchange membrane, without significantly decreasing the electrical conductivity, and improving the ion selectivity.

[0204] In the present application, the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0205] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0206] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A method for preparing a monolayer modified proton exchange membrane, characterized in that: include: dissolving perfluorosulfonic acid resin in a solvent to obtain a polymer solution; Scrape coating the polymer solution into a membrane, followed by a first drying step to obtain a perfluorosulfonic acid proton exchange membrane; Soaking the perfluorosulfonic acid proton exchange membrane in an acid solution containing a single molecule, followed by washing and a second drying to obtain the monolayer-modified proton exchange membrane; The single molecule includes a hydroxyl-terminated compound.

2. The preparation method according to claim 1, characterized in that: The terminal hydroxyl compounds include compounds having the structure of formula I: In formula I, R is one of a hydroxyl group, a saturated hydrocarbon group, an unsaturated hydrocarbon group, an imidazole group, and a phenyl group.

3. The preparation method according to claim 2, characterized in that: The compound having the structure of Formula I includes at least one of Compounds 1 to 5:

4. The preparation method according to claim 1, characterized in that: In the acid solution containing single molecules, the mass content of the terminal hydroxyl compound is 5-10%; and / or, In the acid solution containing single molecules, the acid includes at least one of sulfuric acid and hydrochloric acid; The method for preparing the monolayer-modified proton exchange membrane further comprises the step of preparing an acid solution containing the monomolecule; The method for preparing the acid solution containing the single molecule comprises: dissolving the single molecule in the acid solution and dispersing the single molecule uniformly to obtain the acid solution containing the single molecule.

5. The preparation method according to claim 1, characterized in that: The perfluorosulfonic acid resin includes H-type perfluorosulfonic acid resin; and / or, The solid content of the polymer dispersion is 10-30%; and / or, The solvent includes at least one of water, ethanol and propanol.

6. The preparation method according to claim 1, characterized in that: The base film used in the scraping coating process includes at least one of a polyethylene terephthalate base film, a polyimide base film, and a polyphenylene sulfide base film; and / or, The first drying temperature is 80-160° C., and the first drying time is 10-60 min; and / or, The thickness of the perfluorosulfonic acid proton exchange membrane is 50-60 μm.

7. The preparation method according to claim 1, characterized in that: The soaking time is 0.1-2h; and / or, The soaking temperature is 30-80°C; and / or, During the soaking process, the hydroxyl group at the end of the terminal hydroxyl compound undergoes an esterification reaction with the sulfonic acid group in the perfluorosulfonic acid resin to form an -OSO2- group; and / or, The second drying temperature is 30-80° C., and the second drying time is 8-24 hours; and / or, The detergent used for the washing includes at least one of water, ethanol and propanol.

8. A monolayer modified proton exchange membrane, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7; Preferably, the monolayer in the monolayer-modified proton exchange membrane contains an -OSO2- group, and / or the structural formula of the monolayer in the monolayer-modified proton exchange membrane is as shown in Formula II: In formula II, R' is the perfluorosulfonic acid resin minus the sulfonic acid group, and R is one of a hydroxyl group, a saturated hydrocarbon group, an unsaturated hydrocarbon group, an imidazole group, and a phenyl group; Preferably, the thickness of the monolayer in the monolayer-modified proton exchange membrane is 10-500 nm.

9. A flow battery comprising an electrolyte, an electrode and a diaphragm, characterized in that: The diaphragm is the monolayer modified proton exchange membrane as claimed in claim 8.

10. The liquid flow battery according to claim 9, characterized in that: The liquid flow battery includes one of an all-vanadium liquid flow battery and an iron-chromium liquid flow battery.